Omics Application of Bio-Hydrogen Production Through Green Alga Chlamydomonas reinhardtii - Xu, Lili; Fan, Jianhua; Wang, Quanxi (Frontiers in Bioengineering and Biotechnology, 2019)
This article summarizes the current knowledge regarding omics approaches, which include genomics, transcriptomics, proteomics and metabolomics, in the context of bio-hydrogen production in Chlamydomonas reinhardtii. In this paper, critical genes (HydA1, Hyd A2, Sulp, Tla1, Sta7, PFL1) involved in H2 metabolism were identified and analyzed for their function in H2 accumulation. Furthermore, the advantages of gene microarrays and RNA-seq were compared, as well as their applications in transcriptomic analysis of H2 production. Moreover, as a useful tool, proteomic analysis could identify different proteins that participate in H2 metabolism. This review provides fundamental theory and an experimental basis for H2 production, and further research effort is needed in this field.